A kind of polymer thermal expansion bead and preparation method thereof

Preparation of PMI thermally expanded beads by suspended polymerization has solved the problem of difficult preparation of PMI foam products in the prior art and uneven particles, and achieved uniform particle size and regular shape thermally expanded bead preparation, which has improved foaming performance and lightweight and patterned application value of foam.

CN119039653BActive Publication Date: 2025-04-18CASHEM ADVANCED MATERIALS HI TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411514033.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-04-18
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

It is difficult to directly prepare PMI foam products with complex shapes in the prior art, and traditional methods lead to uneven particle size and irregular shapes, resulting in low foaming ratio, difficulty in bonding between particles, large environmental pollution and a significant reduction in foam performance.

Method used

PMI thermally expanded beads are prepared by suspended polymerization. By adding deionized water, salting agent and dispersion stabilizer to the aqueous phase, a stable mixed liquid is formed, and then polymerized monomers, initiators, copolymerizable foaming agents and crosslinking agents in the oil phase are added. Suspension polymerization is carried out under stirring and nitrogen gas is introduced to prepare thermally expanded beads with suitable particle size.

Benefits of technology

The prepared PMI thermally expanded beads have regular shape, uniform particle size, and good volume expansion ability. They are suitable for lightweight, patterning and three-dimensional applications of materials, and solve the problems of low foaming ratio, difficult particle bonding and environmental pollution in traditional methods, and improve the foam performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application discloses a polymer thermal expansion bead and a preparation method thereof, the method comprising the following steps: preparation of an aqueous phase, the aqueous phase comprising deionized water, a salting-out agent, an aqueous phase inhibitor and a dispersion stabilizer; preparation of an oil phase, the oil phase comprising a polymerization monomer, an initiator, a copolymerizable foaming agent and a crosslinking agent; preparation of PMI thermal expansion beads, the preparation comprising adding the oil phase to the aqueous phase and preparing by suspension polymerization. The present application can provide a thermal expansion bead with a suitable particle size that can be used for in-mold foaming.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of material preparation, and in particular to a method for preparing polymer thermal expansion beads. Background Art

[0002] The current preparation technology is to first polymerize the foamable precursor sheet into a bulk material, and then foam and post-process it at high temperature to form a PMI sheet. This method cannot directly produce PMI foam products with complex shapes. For the preparation of PMI foam parts with complex shapes, secondary processing is required, which is difficult, costly, and wasteful. At present, the industrial solution is to use a mechanical crushing method to crush the foamable precursor sheet and then foam it in a mold. However, this method produces particles of uneven size and irregular shape, resulting in weak interface interactions between adjacent foam particles, low foaming ratio, difficulty in bonding between particles, severe environmental pollution, and greatly reduced foam performance.

[0003] At present, there is a technology that uses suspension polymerization to prepare heat-expandable microspheres, which are then foamed in a mold to obtain corresponding foam products. However, the particle size of microspheres prepared by general suspension polymerization is generally 5-100μm, which is much smaller than the particle size of mechanically crushed copolymer foamable board particles. The particle size is too small, which causes more thermal expansion and adhesion between microspheres, resulting in loss of mechanical properties. At the same time, in suspension polymerization, when the polymerization reaches a certain conversion rate, the monomer becomes a polymer-monomer droplet particle, which has a tendency to stick together and cannot obtain the particle size under the target state. Summary of the invention

[0004] In view of the above technical problems, the purpose of the present application is to provide a heat-expandable bead with suitable particle size that can be used for in-mold foaming.

[0005] Specifically, the present application relates to a method for preparing PMI thermal expansion beads, comprising the following steps:

[0006] Preparation of an aqueous phase, wherein the aqueous phase comprises deionized water, a salting-out agent and a dispersion stabilizer;

[0007] Preparation of an oil phase, wherein the oil phase contains a polymerizable monomer, an initiator, a copolymerizable foaming agent and a crosslinking agent, wherein the polymerizable monomer is acrylic acid and / or methacrylic acid, and acrylonitrile and / or methacrylonitrile;

[0008] The preparation of PMI heat-expandable beads comprises adding an oil phase into a water phase to form a mixed solution, and preparing the beads by suspension polymerization.

[0009] Furthermore, the preparation of the aqueous phase comprises adding deionized water, a salting-out agent and a dispersion stabilizer into a reaction container and stirring, wherein the stirring time is 0.5-1h and the stirring speed is 1000-2000rpm.

[0010] Furthermore, in parts by weight, the deionized water: salting-out agent: dispersion stabilizer is 100:15-20:0.01-3.

[0011] Furthermore, the salting-out agent is selected from one or more of sodium chloride, sodium sulfate and ammonium sulfate.

[0012] Furthermore, the dispersion stabilizer is selected from one or more of nano silicon dioxide, nano magnesium hydroxide, lithium magnesium silicate, kaolin, polyethylene, pyrrolidone, methyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, polyvinyl alcohol, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate.

[0013] More preferably, the dispersion stabilizer is methyl cellulose and lithium magnesium silicate.

[0014] Furthermore, the preparation of the oil phase comprises adding a polymerization monomer, an initiator, a copolymerizable foaming agent and a cross-linking agent into a reaction container and stirring the mixture, wherein the stirring time is 10-30 minutes.

[0015] Furthermore, in parts by weight, the acrylic acid and / or methacrylic acid: acrylonitrile and / or methacrylonitrile: initiator: copolymerizable foaming agent: crosslinking agent = 40-70: 40-70: 0.1-5: 1-20: 0.1-10.

[0016] Furthermore, the initiator is selected from one or more of benzoyl oxide (BPO), dicumyl peroxide (DCP), azobisisobutyronitrile (AIBN), azobisisoheptanenitrile (ABVN), and azobiscyclohexylcarbonitrile (ACCN).

[0017] Furthermore, the copolymerizable foaming agent is selected from one or more of tert-butyl methacrylate, tert-butyl acrylate and isopropyl acrylate.

[0018] Furthermore, the crosslinking agent is selected from one or more of calcium oxide, magnesium oxide, acrylamide (AM), methacrylamide (MAM), allyl methacrylate, metal methacrylate, metal acrylate, allyl acrylate, allyl methacrylate, allyl acrylamide, and allyl methacrylamide.

[0019] Furthermore, in the preparation of the PMI heat-expandable beads, the ratio of the oil phase to the water phase in the mixed solution is 1:4-7, as counted by weight.

[0020] Furthermore, the preparation of the PMI heat-expandable beads also includes adding a polymer dispersant during the suspension polymerization process.

[0021] Furthermore, the polymeric dispersant is selected from nano-silicon dioxide.

[0022] Furthermore, the polymer dispersant is present in an amount of 0.1-5% of the polymer monomer in parts by weight.

[0023] Furthermore, the preparation of the PMI heat expandable beads includes: adding the oil phase to the water phase, stirring for 5-10 minutes, adding a polymer dispersant, and stirring for 10-60 minutes, with a stirring speed of 100-600 r / min, preferably 150-400 r / min, and more preferably 300-350 r / min.

[0024] Furthermore, the preparation of the PMI heat-expandable beads further comprises: introducing nitrogen after stirring, reacting at 50-80° C. for 5-20 hours, washing and drying the discharged material to obtain the PMI heat-expandable beads.

[0025] The present application also relates to PMI heat-expandable beads prepared by the above method, wherein the average particle size of the PMI heat-expandable beads is 0.1-6 mm, preferably 2.5-6 mm.

[0026] Effects of the Invention

[0027] The heat-expandable beads provided in the present application have regular shapes, uniform particle sizes, and good volume expansion capabilities, and have important application value in terms of material lightweighting, patterning, and three-dimensionalization. At the same time, the use of heat-expandable beads for in-mold foaming can solve the problems of low foaming ratio, difficulty in bonding between particles, large environmental pollution, and greatly reduced foam performance when foaming after the precursor sheet is crushed. DETAILED DESCRIPTION

[0028] The present application is further described in detail below in conjunction with specific implementation methods. The examples given are intended to enable a more thorough understanding of the present application and to fully convey the scope of the present application to those skilled in the art.

[0029] It should be noted that certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that technicians may use different nouns to refer to the same component. This specification and claims do not use the difference in nouns as a way to distinguish components, but use the functional differences of components as the criterion for distinction. As mentioned throughout the specification and claims, "including" or "comprising" are open-ended terms and should be interpreted as "including but not limited to". The subsequent description of the specification is a preferred embodiment of the present application, but the description is based on the general principles of the specification and is not intended to limit the scope of the present application. The scope of protection of the present application shall be determined by the attached claims.

[0030] One aspect of the present application provides a method for preparing PMI heat-expandable beads, comprising the following steps:

[0031] Preparation of an aqueous phase, wherein the aqueous phase comprises deionized water, a salting-out agent and a dispersion stabilizer;

[0032] Preparation of an oil phase, wherein the oil phase contains a polymerizable monomer, an initiator, a copolymerizable foaming agent and a crosslinking agent, wherein the polymerizable monomer is acrylic acid and / or methacrylic acid, and acrylonitrile and / or methacrylonitrile;

[0033] The preparation of PMI heat-expandable beads comprises adding an oil phase into a water phase to form a mixed solution, and preparing the beads by suspension polymerization.

[0034] In a specific embodiment, the step of preparing the aqueous phase comprises:

[0035] Deionized water, salting-out agent and dispersion stabilizer are added into the reaction container and stirred.

[0036] In a specific embodiment, the stirring time is 0.5-1h.

[0037] In a specific embodiment, the stirring speed is 1000-2000 rpm.

[0038] In a specific implementation, the ratio of deionized water: salting-out agent: dispersion stabilizer is 100:15-20:0.01-3 in parts by weight.

[0039] For example, in some specific embodiments, the ratio of deionized water: salting-out agent: dispersion stabilizer is 100:15-18:0.01-0.1, or 100:15-18:0.1-1, or 100:18-20:1-2, or 100:18-20:1-3, etc., counted in parts by weight.

[0040] In a specific embodiment, the salting-out agent is selected from one or more of sodium chloride, sodium sulfate and ammonium sulfate.

[0041] The addition of the salting-out agent can effectively inhibit the excessive polymerization of the monomer in the aqueous phase during the suspension polymerization process, preventing the product from flocculating and agglomerating, thereby preventing the formation of suitable beads.

[0042] In a specific embodiment, the dispersion stabilizer is selected from one or more of nano-silicon dioxide, nano-magnesium hydroxide, lithium magnesium silicate, kaolin, polyethylene, pyrrolidone, methyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, polyvinyl alcohol, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate.

[0043] In a preferred embodiment, the dispersion stabilizer is methyl cellulose and lithium magnesium silicate.

[0044] In a specific embodiment, the ratio of methyl cellulose to lithium magnesium silicate in the dispersion stabilizer is 1-5:1, for example, 1:1, 2:1, 3:1, 4:1 or 5:1.

[0045] The addition of a dispersion stabilizer can effectively control the rate of the initial suspension polymerization reaction, avoiding the adverse effects of too fast a reaction on the morphology and particle size of the beads formed, so as to obtain beads with high stability, regular particle shape and appropriate particle size.

[0046] In a specific embodiment, the preparation step of the oil phase comprises:

[0047] Add the polymerization monomer, initiator, copolymerizable foaming agent and cross-linking agent into a reaction container and stir for 10-30 minutes.

[0048] In a specific embodiment, the stirring time is 10-30 min.

[0049] In a specific embodiment, the acrylic acid and / or methacrylic acid: acrylonitrile and / or methacrylonitrile: initiator: copolymerizable foaming agent: crosslinking agent = 40-70: 40-70: 0.1-5: 1-20: 0.1-10 in parts by weight.

[0050] In a specific embodiment, the initiator is selected from one or more of benzoyl oxide (BPO), dicumyl peroxide (DCP), azobisisobutyronitrile (AIBN), azobisisoheptanenitrile (ABVN), and azobiscyclohexylcarbonitrile (ACCN).

[0051] In a specific embodiment, the copolymerizable foaming agent is selected from one or more of tert-butyl methacrylate, tert-butyl acrylate, and isopropyl acrylate.

[0052] In a specific embodiment, the crosslinking agent is selected from one or more of calcium oxide, magnesium oxide, acrylamide (AM), methacrylamide (MAM), allyl methacrylate, metal methacrylate, metal acrylate, allyl acrylate, allyl methacrylate, allyl acrylamide, and allyl methacrylamide.

[0053] In a specific embodiment, in the preparation of the PMI heat-expandable beads, the ratio of oil phase to water phase in the mixed solution is 1:4-7, for example, 1:4, 1:5, 1:6 or 1:7.

[0054] In a specific embodiment, the preparation of the PMI heat-expandable beads further comprises adding a polymer dispersant during the suspension polymerization process.

[0055] In a specific embodiment, the polymeric dispersant is selected from nano-silica.

[0056] By adding a certain amount of dispersant again during the suspension polymerization process, the reaction rate can be adjusted in time according to the progress of the polymerization reaction, and the size and stability of the formed beads can be further adjusted.

[0057] In a specific embodiment, the polymeric dispersant is appropriately added according to the amount of the polymerized monomers in the reaction. In a specific embodiment, the polymeric dispersant is 0.1-5% of the polymerized monomers in parts by weight.

[0058] In a specific embodiment provided in the present application, the preparation of the PMI heat-expandable beads comprises the following steps:

[0059] The oil phase is added to the water phase, stirred for 5-10 minutes, and then the polymer dispersant is added, followed by stirring for another 10-60 minutes.

[0060] In a specific embodiment, the stirring speed is 100-600 r / min, for example, 100 r / min, 150 r / min, 200 r / min, 250 r / min, 300 r / min, 350 r / min, 400 r / min, 450 r / min, 500 r / min, 550 r / min, 600 r / min.

[0061] In a specific embodiment, the stirring speed has an effect on the molding state of the beads and the size of the formed particles. In practice, by adjusting the speed, a suitable bead size can be obtained. In some specific embodiments, a bead size suitable for foaming can be obtained at a rotation speed of about 350 r / min. The stirring speed should not be too fast. During the stirring and shearing process, a faster stirring speed will cause the small droplets to be unable to agglomerate, which will reduce the bead size and make the particle size distribution narrower.

[0062] In some specific embodiments, the preparation of the PMI heat-expandable beads further comprises the following steps:

[0063] After stirring, nitrogen is introduced, and the reaction is carried out at 50-80° C. for 5-20 hours. The discharged material is washed and dried to obtain the PMI heat-expandable beads.

[0064] One aspect of the present application also provides PMI heat-expandable beads prepared by the above method.

[0065] In a specific embodiment, the particle size of the obtained PMI heat-expandable beads is 0.1-6 mm.

[0066] In some specific embodiments, the particle size of the beads is 3-6 mm. In some specific embodiments, the particle size of the beads is 1-3 mm. In some specific embodiments, the particle size of the beads is 0.1-1 mm.

[0067] In the technical solution of the present application, the oil phase and the water phase are evenly dispersed by a dispersing stabilizer, and the monomer is distributed in the water phase in the form of droplets for polymerization. Compared with bulk polymerization, it can quickly transfer heat, avoid implosion, and ensure the stability of product performance. The monomer is broken up under stirring, and then forms small droplets under the action of surface tension. The small droplets continue to collide and condense into large droplets under stirring, and then are broken up into small droplets again. The "small droplets-large droplets-small droplets" cycle is repeated, and after a period of time, it is in dynamic equilibrium, forming a stable droplet dispersion system that can exist.

[0068] Adding a salting-out agent into the aqueous phase can effectively inhibit the polymerization of monomers in the aqueous phase through the salting-out effect, thereby preventing the resulting product from flocculating and agglomerating.

[0069] Adding the dispersant in steps can not only prevent the reaction from being too intense in the early stage of the reaction, which may lead to the formation of agglomerates of the product, but also further adjust the rate according to the progress of the reaction, making the reaction more stable and conducive to the formation of bead products with good morphology and suitable particle size.

[0070] Example

[0071] The present application provides a general and / or specific description of the materials and test methods used in the experiments. In the following examples, unless otherwise specified, % represents wt%, i.e., weight percentage. Unless otherwise specified, the reagents and instruments used are conventional reagent products or conventional experimental instruments that can be purchased commercially.

[0072] Example 1 Preparation of PMI thermal expansion beads

[0073] (1) Preparation of aqueous phase: Deionized water, aqueous phase salting-out agent (sodium chloride), and dispersion stabilizer (methyl cellulose and lithium magnesium silicate 3:1) were added to the reaction vessel in sequence and stirred for 20 minutes. The raw material composition (by mass) was: 590 parts of deionized water, 101 parts of aqueous phase salting-out agent, and 10 parts of dispersion stabilizer.

[0074] (2) Preparation of oil phase: polymerizable monomers (methacrylic acid and methacrylonitrile), initiator (azobisisobutyronitrile), copolymerizable foaming agent (tert-butyl acrylate), and crosslinking agent (acrylamide) are added to the reaction vessel in sequence and stirred at 1300 rpm for 45 min. The raw material composition (by mass) is: 70 parts of methacrylic acid, 50 parts of methacrylonitrile, 0.7 parts of initiator, 15 parts of copolymerizable foaming agent, and 3.5 parts of crosslinking agent.

[0075] (3) Suspension polymerization: The oil phase obtained in the above step is added to the water phase, and the oil phase: water phase is 1:5 by weight. The rotation speed is set to 350 r / min, and after mechanical stirring for 8 minutes, a polymerization dispersant (nanosilica) of 1% of the total weight of the polymerization monomer is added, and then stirred for another 30 minutes. Nitrogen is introduced, and the reaction is carried out at a temperature of 70°C for 8 hours. The material is discharged, washed, filtered, and dried to obtain thermal expansion beads.

[0076] Example 2 Preparation of PMI thermal expansion beads

[0077] (1) Preparation of aqueous phase: Deionized water, aqueous phase salting-out agent (sodium chloride), and dispersion stabilizer (sodium dodecyl sulfate) are added to the reaction vessel in sequence and stirred for 20 minutes. The raw material composition (by mass) is: 590 parts of deionized water, 101 parts of aqueous phase salting-out agent, and 10 parts of dispersion stabilizer.

[0078] (2) Preparation of oil phase: polymerizable monomers (methacrylic acid and methacrylonitrile), initiator (azobisisobutyronitrile), copolymerizable foaming agent (tert-butyl acrylate), and crosslinking agent (acrylamide) are added to the reaction vessel in sequence and stirred at 1300 rpm for 45 min. The raw material composition (by mass) is: 70 parts of methacrylic acid, 50 parts of methacrylonitrile, 0.7 parts of initiator, 15 parts of copolymerizable foaming agent, and 3.5 parts of crosslinking agent.

[0079] (3) Suspension polymerization: The oil phase obtained in the above step is added to the water phase, and the oil phase: water phase is 1:5 by weight. The rotation speed is set to 350 r / min, and after mechanical stirring for 8 minutes, a polymerization dispersant (nanosilica) of 1% of the total weight of the polymerization monomer is added, and then stirred for another 30 minutes. Nitrogen is introduced, and the reaction is carried out at a temperature of 70°C for 8 hours. The material is discharged, washed, filtered, and dried to obtain thermal expansion beads.

[0080] Example 3 Preparation of PMI thermal expansion beads

[0081] (1) Preparation of aqueous phase: Deionized water, aqueous phase salting-out agent (sodium chloride), and dispersion stabilizer (hydroxypropyl methylcellulose) are added to the reaction vessel in sequence and stirred for 20 minutes. The raw material composition (by mass) is: 590 parts of deionized water, 101 parts of aqueous phase salting-out agent, and 10 parts of dispersion stabilizer.

[0082] (2) Preparation of oil phase: polymerizable monomers (methacrylic acid and methacrylonitrile), initiator (azobisisobutyronitrile), copolymerizable foaming agent (tert-butyl acrylate), and crosslinking agent (acrylamide) are added to the reaction vessel in sequence and stirred at 1300 rpm for 45 min. The raw material composition (by mass) is: 70 parts of methacrylic acid, 50 parts of methacrylonitrile, 0.7 parts of initiator, 15 parts of copolymerizable foaming agent, and 3.5 parts of crosslinking agent.

[0083] (3) Suspension polymerization: The oil phase obtained in the above step is added to the water phase, and the oil phase: water phase is 1:5 by weight. The rotation speed is set to 350 r / min, and after mechanical stirring for 8 minutes, a polymerization dispersant (nanosilica) of 1% of the total weight of the polymerization monomer is added, and then stirred for another 30 minutes. Nitrogen is introduced, and the reaction is carried out at a temperature of 70°C for 8 hours. The material is discharged, washed, filtered, and dried to obtain thermal expansion beads.

[0084] Example 4 Preparation of PMI thermal expansion beads

[0085] (1) Preparation of aqueous phase: Deionized water, aqueous phase salting-out agent (sodium chloride), and dispersion stabilizer (methyl cellulose and lithium magnesium silicate 2:1) were added to the reaction vessel in sequence and stirred for 20 minutes. The raw material composition (by mass) was: 590 parts of deionized water, 101 parts of aqueous phase salting-out agent, and 5 parts of dispersion stabilizer.

[0086] (2) Preparation of oil phase: polymerizable monomers (methacrylic acid and methacrylonitrile), initiator (azobisisobutyronitrile), copolymerizable foaming agent (tert-butyl acrylate), and crosslinking agent (acrylamide) are added to the reaction vessel in sequence and stirred at 1300 rpm for 45 min. The raw material composition (by mass) is: 70 parts of methacrylic acid, 50 parts of methacrylonitrile, 0.7 parts of initiator, 15 parts of copolymerizable foaming agent, and 3.5 parts of crosslinking agent.

[0087] (3) Suspension polymerization: The oil phase obtained in the above step is added to the water phase, and the oil phase: water phase is 1:5 by weight. The rotation speed is set to 350 r / min, and after mechanical stirring for 8 minutes, a polymerization dispersant (nanosilica) of 1% of the total weight of the polymerization monomer is added, and then stirred for another 30 minutes. Nitrogen is introduced, and the reaction is carried out at a temperature of 70°C for 8 hours. The material is discharged, washed, filtered, and dried to obtain thermal expansion beads.

[0088] Example 5 Preparation of PMI heat-expandable beads

[0089] (1) Preparation of aqueous phase: Deionized water, aqueous phase salting-out agent (sodium chloride), and dispersion stabilizer (methyl cellulose and lithium magnesium silicate in a ratio of 3:1) were added to the reaction vessel in sequence and stirred for 20 minutes. The raw material composition (by mass) was: 590 parts of deionized water, 101 parts of aqueous phase salting-out agent, and (10) parts of dispersion stabilizer.

[0090] (2) Preparation of oil phase: polymerizable monomers (methacrylic acid and methacrylonitrile), initiator (azobisisobutyronitrile), copolymerizable foaming agent (tert-butyl acrylate), and crosslinking agent (acrylamide) are added to the reaction vessel in sequence and stirred at 1300 rpm for 45 min. The raw material composition (by mass) is: 70 parts of methacrylic acid, 50 parts of methacrylonitrile, 0.7 parts of initiator, 15 parts of copolymerizable foaming agent, and 3.5 parts of crosslinking agent.

[0091] (3) Suspension polymerization: The oil phase obtained in the above step is added to the water phase, and the oil phase: water phase is 1:5 by weight. The rotation speed is set to 500 r / min, and after mechanical stirring for 8 minutes, a polymerization dispersant (nanosilica) of 1% of the total weight of the polymerization monomer is added, and then stirred for another 30 minutes. Nitrogen is introduced, and the reaction is carried out at a temperature of 70°C for 8 hours. The material is discharged, washed, filtered, and dried to obtain thermal expansion beads.

[0092] Example 6 Preparation of PMI thermal expansion beads

[0093] (1) Preparation of aqueous phase: Deionized water, aqueous phase salting-out agent (sodium chloride), and dispersion stabilizer (methyl cellulose and lithium magnesium silicate 3:1) were added to the reaction vessel in sequence and stirred for 20 minutes. The raw material composition (by mass) was: 590 parts of deionized water, 101 parts of aqueous phase salting-out agent, and 10 parts of dispersion stabilizer.

[0094] (2) Preparation of oil phase: polymerizable monomers (methacrylic acid and methacrylonitrile), initiator (azobisisobutyronitrile), copolymerizable foaming agent (tert-butyl acrylate), and crosslinking agent (acrylamide) are added to the reaction vessel in sequence and stirred at 1300 rpm for 45 min. The raw material composition (by mass) is: 70 parts of methacrylic acid, 50 parts of methacrylonitrile, 0.7 parts of initiator, 15 parts of copolymerizable foaming agent, and 3.5 parts of crosslinking agent.

[0095] (3) Suspension polymerization: The oil phase obtained in the above step is added to the water phase, and the weight ratio is 1:5. The rotation speed is set to 200 r / min, and after mechanical stirring for 8 minutes, a polymerization dispersant (nanosilica) of 1% of the total weight of the polymerization monomer is added, and then stirred for another 30 minutes. Nitrogen is introduced, and the reaction is carried out at a temperature of 70°C for 8 hours. The material is discharged, washed, filtered, and dried to obtain thermal expansion beads.

[0096] Comparative Example 1 Preparation of PMI thermal expansion beads

[0097] (1) Preparation of aqueous phase: Deionized water, aqueous phase salting-out agent (sodium chloride), and dispersion stabilizer (methyl cellulose and lithium magnesium silicate 3:1) were added to the reaction vessel in sequence and stirred for 20 minutes. The raw material composition (by mass) was: 590 parts of deionized water, 101 parts of aqueous phase salting-out agent, and 10 parts of dispersion stabilizer.

[0098] (2) Preparation of oil phase: polymerizable monomers (methacrylic acid and methacrylonitrile), initiator (azobisisobutyronitrile), copolymerizable foaming agent (tert-butyl acrylate), and crosslinking agent (acrylamide) are added to the reaction vessel in sequence and stirred at 1300 rpm for 45 min. The raw material composition (by mass) is: 70 parts of methacrylic acid, 50 parts of methacrylonitrile, 0.7 parts of initiator, 15 parts of copolymerizable foaming agent, and 3.5 parts of crosslinking agent.

[0099] (3) Suspension polymerization: The oil phase obtained in the above step is added to the water phase, and the oil phase: water phase is 1:5 by weight. The speed is set to 350 r / min, and after mechanical stirring for 40 minutes, nitrogen is introduced, and the temperature is 70°C for 8 hours. The material is discharged, washed, filtered, and dried to obtain thermal expansion beads.

[0100] Comparative Example 2 Preparation of PMI heat-expandable beads

[0101] (1) Preparation of aqueous phase: Deionized water, aqueous phase salting agent (sodium chloride), and dispersion stabilizer (methyl cellulose and lithium magnesium silicate 3:1) were added to the reaction vessel in sequence and stirred for 20 minutes. The raw material composition (by mass) was: 360 parts of deionized water, 55 parts of aqueous phase salting agent, and 3 parts of dispersion stabilizer.

[0102] (2) Preparation of oil phase: polymerizable monomers (methacrylic acid and methacrylonitrile), initiator (azobisisobutyronitrile), copolymerizable foaming agent (tert-butyl acrylate), and crosslinking agent (acrylamide) are added to the reaction vessel in sequence and stirred at 1300 rpm for 45 min. The raw material composition (by mass) is: 70 parts of methacrylic acid, 50 parts of methacrylonitrile, 0.7 parts of initiator, 15 parts of copolymerizable foaming agent, and 3.5 parts of crosslinking agent.

[0103] (3) Suspension polymerization: The oil phase obtained in the above step is added to the water phase, and the weight ratio of oil phase: water phase is 1:3. The rotation speed is set to 350 r / min, and after mechanical stirring for 8 minutes, a polymerization dispersant (nanosilica) of 1% of the total weight of the polymerization monomer is added, and then stirred for another 30 minutes. Nitrogen is introduced, and the reaction is carried out at a temperature of 70°C for 8 hours. The material is discharged, washed, filtered, and dried to obtain thermal expansion beads.

[0104] Comparative Example 3 Preparation of PMI thermal expansion beads

[0105] (1) Preparation of aqueous phase: Deionized water, aqueous phase salting-out agent (sodium chloride), and dispersion stabilizer (methyl cellulose and lithium magnesium silicate 3:1) were added to the reaction vessel in sequence and stirred for 20 minutes. The raw material composition (by mass) was: 590 parts of deionized water, 101 parts of aqueous phase salting-out agent, and 10 parts of dispersion stabilizer.

[0106] (2) Preparation of oil phase: polymerizable monomers (methacrylic acid and methacrylonitrile), initiator (azobisisobutyronitrile), copolymerizable foaming agent (tert-butyl acrylate), and crosslinking agent (acrylamide) are added to the reaction vessel in sequence and stirred at 1300 rpm for 45 min. The raw material composition (by mass) is: 70 parts of methacrylic acid, 50 parts of methacrylonitrile, 0.7 parts of initiator, 15 parts of copolymerizable foaming agent, and 3.5 parts of crosslinking agent.

[0107] (3) Suspension polymerization: The oil phase obtained in the above step is added to the water phase, and the oil phase: water phase is 1:5 by weight. The rotation speed is set to 800 r / min, and after mechanical stirring for 8 minutes, a polymerization dispersant (nanosilica) of 1% of the total weight of the polymerization monomer is added, and then stirred for another 30 minutes. Nitrogen is introduced, and the reaction is carried out at a temperature of 70°C for 8 hours. The material is discharged, washed, filtered, and dried to obtain thermal expansion beads.

[0108] Experimental Example 1 PMI thermal expansion bead particle size test

[0109] The particle size of the heat-expandable bead samples obtained in the above examples and comparative examples was measured by sieving. The particles to be tested were passed through a series of sieves with different apertures, and the particle size range of the particles was determined based on whether the particles could pass through the sieves. The shape and agglomeration state of the beads were observed. The specific results are shown in Table 1.

[0110] Experimental Example 2 Determination of Foaming Molding Performance of PMI Thermally Expandable Beads

[0111] Foaming of PMI heat-expandable beads: The PMI heat-expandable beads obtained in the above Examples 1-6 and Comparative Examples 1-3 are foamed respectively, and the specific steps are: filling the beads into the inner cavity of the mold, raising the temperature of the foaming mold according to a program, first preheating from room temperature to 160°C for 0.5 to 2 hours, and then foaming and curing at 120 to 240°C for 0.5 to 12 hours, the material expands and foams, fills the mold cavity, and is completely cured; cooling and demolding; obtaining a special-shaped product.

[0112] At the same time, a PMI prepolymer was prepared and foamed under the same process. The specific method was as follows: 70 parts of methacrylonitrile, 50 parts of methacrylic acid, 0.7 parts of azobisisobutyronitrile, 15 parts of tert-butyl acrylate, and 3.5 parts of acrylamide were mixed evenly, and polymerized at 45°C for 150 hours to obtain a PMI prepolymer. A PMI prepolymer crusher with a power of 30 kw was used to crush the prepolymer. The crushed particles were filled into the inner cavity of the mold, and the foaming mold was heated according to the program, first preheated from room temperature to 160°C for 0.5 to 2 hours, and then foamed and cured at 120 to 240°C for 0.5 to 12 hours, the material expanded and foamed, filled the mold cavity, and was completely cured; cooled and demolded; and a special-shaped product was obtained (Comparative Example 4).

[0113] The density of the special-shaped foamed samples of Examples 1-6 and Comparative Examples 1-4 obtained above was measured according to GB / T 6343-2009 Determination of apparent density of foamed plastics and rubber to check their foaming properties. The results are shown in Table 1.

[0114] Experimental Example 3 Determination of Mechanical Properties of Foam Material Prepared from PMI Thermally Expanded Beads

[0115] The mechanical properties of the various shaped foam samples obtained in Experimental Example 2 were measured, wherein the tensile strength was measured in accordance with ASTM-D638-2010 Plastic Tensile Strength, and the compressive strength was measured in accordance with GB / T 8813-2008 Determination of Compression Properties of Rigid Foam Plastics. The results are shown in Table 1.

[0116] .

[0117] It can be seen from the above experimental results that the preparation method of the present application can effectively reduce the agglomeration of droplets during suspension polymerization, and obtain spherical beads with relatively uniform particle size and regular shape. By selecting suitable dispersant types and adjusting conditions such as the rotation speed during suspension polymerization, beads with relatively large particle size can be obtained, which are more suitable for in-mold foaming processes. Furthermore, the special-shaped components prepared by foaming the obtained beads also have relatively excellent mechanical properties.

[0118] The above is only the preferred embodiment of the present application, and does not limit the present application in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment based on the technical essence of the present application without departing from the technical solution of the present application still falls within the protection scope of the technical solution of the present application.

Claims

1. A method for preparing PMI thermal expansion beads, comprising the following steps: Preparation of an aqueous phase, wherein the aqueous phase comprises deionized water, a salting-out agent and a dispersion stabilizer, wherein the dispersion stabilizer is methyl cellulose and lithium magnesium silicate; Preparation of an oil phase, wherein the oil phase contains a polymerizable monomer, an initiator, a copolymerizable foaming agent and a crosslinking agent, wherein the polymerizable monomer is acrylic acid and / or methacrylic acid, and acrylonitrile and / or methacrylonitrile; Preparation of PMI thermal expansion beads, the preparation comprising adding an oil phase into an aqueous phase to form a mixed solution, adding a polymer dispersant into the mixed solution, and preparing the beads by suspension polymerization. Wherein, the ratio of oil phase to water phase in the mixed solution is 1:4-7. During the preparation of the PMI heat-expandable beads, the oil phase is added to the water phase and stirred for 5-10 minutes, then the polymer dispersant is added and stirred for another 10-60 minutes at a stirring speed of 250-450 r / min. The polymer dispersant is nano silicon dioxide.

2. The method according to claim 1, wherein: The preparation of the aqueous phase comprises adding deionized water, a salting-out agent and a dispersion stabilizer into a reaction container and stirring. The stirring time is 0.5-1h and the stirring speed is 1000-2000rpm.

3. The method according to claim 1, wherein: In parts by weight, the deionized water: salting-out agent: dispersion stabilizer is 100:15-20:0.01-3.

4. The method according to claim 1, wherein: The salting-out agent is selected from one or more of sodium chloride, sodium sulfate and ammonium sulfate.

5. The method according to claim 1, wherein: The preparation of the oil phase comprises adding a polymerization monomer, an initiator, a copolymerizable foaming agent and a cross-linking agent into a reaction container and stirring the mixture. The stirring time is 10-30 minutes.

6. The method according to claim 1, wherein: In parts by weight, the acrylic acid and / or methacrylic acid: acrylonitrile and / or methacrylonitrile: initiator: copolymerizable foaming agent: crosslinking agent=40-70:40-70:0.1-5:1-20:0.1-10.

7. The method according to claim 1, wherein: The initiator is selected from one or more of benzoyl oxide (BPO), diisopropylbenzene peroxide (DCP), azobisisobutyronitrile (AIBN), azobisisoheptanenitrile (ABVN), and azobiscyclohexylcarbonitrile (ACCN), and / or the copolymerizable foaming agent is selected from one or more of tert-butyl methacrylate, tert-butyl acrylate, and isopropyl acrylate, and / or the cross-linking agent is selected from one or more of calcium oxide, magnesium oxide, acrylamide (AM), methacrylamide (MAM), allyl methacrylate, metal methacrylate, metal acrylate, allyl acrylate, allyl methacrylate, allyl acrylamide, and allyl methacrylamide.

8. The method according to claim 1, wherein: In parts by weight, the polymer dispersant is 0.1-5% of the polymer monomer.

9. The method according to claim 1, wherein: The preparation of the PMI heat-expandable beads further comprises: introducing nitrogen after stirring, reacting at 50-80° C. for 5-20 hours, washing and drying the discharged material to obtain the PMI heat-expandable beads.

10. The PMI heat-expandable beads prepared according to the method according to any one of claims 1 to 9, wherein the average particle size of the PMI heat-expandable beads is 0.1-6 mm.

Citation Information

Patent Citations

  • Polyfunctional alcohols as cross-linkers in pmi foams

    CN108026308A

  • PMI block foam material and preparation method thereof

    CN114230952A

  • Thermal expansion microsphere capable of rapidly foaming in short temperature range as well as preparation method and application of thermal expansion microsphere

    CN118240262A